A study of Masai herds on Elangata Wuas group ranch in Kajiado district, Kenya - Semenye, P.P. (International Livestock Centre for Africa, 1980)
Survey results rel. to Masai herds on Elangata Wuas group ranch, particularly showing body measurements and live weights of zebu and crossbred cattle, herd structure, calving rates, preweaning mortality and grazing behaviour of cattle, sheep and goats.